Issues and Management of Islamic Education in a Global Context - Husna Amin; Gairah Sinulingga; Desy Desy; Erjati Abas; Sukarno Sukarno (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The issue of Islamic education management governance in global education is the main objective of this secondary data review. To complete the discussion of this study, we have collected a series of data and literature on several data sources electronically in educational journal publications, book proceedings, and website databases that actively voice Islamic education issues in a global context. We cannot describe the data that we collect directly. We analyze it using various approaches, such as sharp evaluation coding and drawing conclusions that can answer the essence of the problems of this book review. The data we take online is as much as possible to look for the more up-to-date ones published in the last ten years. Finally, we can conclude that based on the findings and discussion data, among others, issues relating to the governance of Islamic religious education still leave problems and challenges, including the difficulty of achieving quality education due to issues of teacher resources that are still low in the mastery of technology that is still lacking. Straightforward access to education is still unequal, and issues related to leadership and school leadership in general education and the Islamic religion. We hope that these results will be a meaningful input in developing studies related to issues and governance of education management that will be held in the future.